N Dimensional Finite Wavelet Filters (Journal of Computational Mathematics, 2021)
In this paper, a large class of $n$ dimensional orthogonal and biorthogonal wavelet filters (lowpass and highpass) are presented in explicit expression. We also characterize orthogonal filters with linear phase in this case. Some examples are also given, including nonseparable orthogonal and biorthogonal filters with linear phase.
Keywords: $n$ Dimension; Linear phase; Wavelet filters.